Metabolite Profile of arabica Coffee Cascara from Typica Cultivar in Bandung with Different Drying Processes - Sururi, Zaki Fahreza; Diana, Sariwulan; Kusdianti, Kusdianti (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2025)
Arabica coffee bean (Coffea arabica L.) is Indonesia's leading commodity, with Bandung Regency as the largest producer in West Java. The exocarp and mesocarp of coffee fruits known as cascara have potential health benefits as a beverage. Cascara is usually dried by direct sunlight before consumption, but this process is prone to weather disturbances and contamination. The use of dehydrators is more controlled to maintain metabolite content, but there has been no research on cascara from coffee cultivars in Bandung Regency dried by this method. This study aims to obtain the metabolite profile of Typica arabica coffee cultivar cascara dried using direct sun and dehydrator. The cascara samples were taken from Gunung Puntang Coffee Plantation, Bandung Regency, and extracted using maceration method with 70% ethanol p.a. solvent. The metabolite content was analyzed by Gas Chromatography-Mass Spectrometry (GC-MS), which specifically detects volatile metabolites. Non-volatile compounds were not within the scope of this study. The results showed that direct sun-dried cascara had 6 metabolites, while dehydrator-dried had 15 metabolites. Both samples were dominated by caffeine (sun-dried cascara: 46.61%, dehydrator cascara: 24.44%). Five metabolites were found in both samples, with 1 unique metabolite in solar cascara and 10 unique metabolites in dehydrator cascara. This study showed differences in metabolite content in Typica cultivar cascara with different drying methods.